Protease Dependent Activation of Endothelial Cells by Peritoneal Dialysis Effluents - Krebs, Michael; Kaun, Christoph; Lorenz, Matthias; Haag-Weber, Marianne; Geiger, Margarethe; Binder, Bernd R. (Thrombosis and Haemostasis, 1999)
Incubation of cultured human umbilical vein endothelial cells (HUVECs) with dilutions of peritoneal dialysis effluents (PDEs) from 11 individual patients undergoing continuous ambulatory peritoneal dialysis (CAPD) induced cellular procoagulant activity in a dose and time dependent manner. This procoagulant activity could be attributed to tissue factor (TF) expression since it was blocked by rabbit anti-TF IgG. These data was confirmed by FACS analysis yielding surface TF expression; In addition PDEs induced the expression of E-selectin in HUVECs. This TF and selectin inducing activity was heat labile and could be inhibited by protease inhibitors. Partial purification could be achieved using a benzamidine-Sepharose column. The TF inducing activity could not be attributed to LPS, IL-1, TNF-α, mast cell tryptase, active thrombin, or complement factor D. We therefore conclude that the peritoneal cavity contains a protease activity that induces a procoagulatory and proinflammatory phenotype in HUVECs.
Keywords: Peritoneal dialysis; endothelial cells; tissue factor; adhesion molecules